(Un)making in sustainability transformation beyond capitalism. (July 2021) - Feola, Giuseppe; Koretskaya, Olga; Moore, Danika
Highlights: Transformation deconstructs capitalist modernity and constructs postcapitalist realities. Evidence of these processes in the territorios campesinos agroalimentarios movement. A research agenda that calls for plural engagement across the social sciences and humanities. Abstract: Theorizations of sustainability transformation have foregrounded the construction (making) of novel socioecological relations; however, they generally have obscured processes of deliberate deconstruction (unmaking) of existing, unsustainable ones. Amidst ever more compelling evidence of the simultaneous unsustainability and continued reproduction of capitalist modernity, it is misguided to assume that transformation can happen by the mere construction of supposed 'solutions', be they technological, social or cultural. We rather need to better understand whether and how existing institutions, forms of knowledge, practices, imaginaries, power structures, and human-non-human relations can be deconstructed at the service of sustainability transformation. This paper demonstrates the usefulness of a lens that attends to processes of making and unmaking in sustainability transformations through an analysis of an ongoing sustainability transformation, the territorios campesinos agroalimentarios (TCA) endogenous territorial figure and peasant movement in Colombia. TCA is transforming territory beyond capitalism on the basis of relational ontologies and principles of autonomy, dignity and sufficiency. This paper identifies processes of unmaking of capitalism in the TCA and demonstrates how they are concretely entangled in the construction of post-capitalist realities. This paper sketches a research agenda on sustainability transformation that is sensitive to and theoretically equipped for the analysis of transformation as a multifaceted, multilevel process that entails the deconstruction of capitalist modernity and the construction of post-capitalist realities. Central to this agenda is a plural engagement with theories of social change from across the social sciences and humanities, which have not previously been mobilized for this endeavour.